Cigarette acquisition and proof of age among US high school students who smoke. Issue 1 (1st March 2002) - Jones, S Everett; Sharp, D J; Husten, C G; Crossett, L S
Abstract : Objective: To determine how US high school students who are under 18 years of age and who smoke obtain their cigarettes and whether they are asked for proof of age. Design and setting: Data from the Centers for Disease Control and Prevention's 1995, 1997, and 1999 national Youth Risk Behavior Surveys which employed national probability samples of students in grades 9–12 (ages 14–18 years). Main outcome measures: Associations of usual source of cigarettes and request for proof of age with variables such as sex, race/ethnicity, grade, and frequency of smoking. Results: In 1999, among current smokers under age 18 years, 23.5% (95% confidence interval (CI), −4.5% to +4.5%) usually purchased their cigarettes in a store; among these students, 69.6% (95% CI −5.7% to +5.7%) were not asked to show proof of age. As days of past month smoking increased, reliance on buying cigarettes in a store (p < 0.001) and giving someone else money to buy cigarettes (p < 0.001) increased, and usually borrowing cigarettes decreased (p < 0.001). From 1995 to 1999, relying on store purchases significantly decreased (from 38.7% (95% CI −4.6% to + 4.6%) to 23.5% (95% CI −4.5% to +4.5%)); usually giving someone else money to buy cigarettes significantly increased (from 15.8% (95% CI −3.6% to +3.6%) to 29.9% (95% CI −4.5% to + 4.5%)). Conclusions: Stricter enforcement of tobacco access laws is needed to support other community and school efforts to reduce tobacco use among youth. Furthermore, effective interventions to reduce non-commercial sources of tobacco, including social, need to be developed and implemented.